The Effect of Cananga (Cananga odorata) Aromatherapy on Anxiety Level of Patients Before Tooth Extraction in RSGM-P USU: Pengaruh Aromaterapi Kenanga (Cananga odorata) Terhadap Tingkat Kecemasan Pasien Sebelum Pencabutan Gigi Posterior di RSGM USU - Isnandar; Abdullah Oes; Indra Basar; Mutia Firenza (TALENTA, 2021)
Tooth extraction is a form of treatment in dentistry. Tooth extraction has the potential to cause excessive anxiety in patients because patients tend to think about things that will or can happen during the procedure. The purpose of this study was to determine the effect of Cananga aromatherapy (Cananga odorata) on the anxiety level of patients at RSGM USU. This research method is a quasi-experimental study using a re-experimental design non-randomized pretest and posttest control group design. The sample was divided into 2 groups, namely the treatment group and the control group. Each group consists of 16 people who will extract the posterior teeth of the upper and/or lower jaw. The treatment group was given a Cananga aromatherapy nasal inhaler and the control group was given an empty nasal inhaler without Cananga aromatherapy. Blood pressure and pulse measurements were taken twice. The first measurement after the patient was given informed consent and the MDAS questionnaire (Modified Dental Anxiety Scale) and the second measurement after inhaling the Cananga aromatherapy nasal inhaler and empty nasal inhaler without Cananga aromatherapy within 10 cm from the nasal cavity for 5 minutes. The results of this study were analyzed using the Wilcoxon and Mann-Whitney tests. In the treatment group, there was a significant decrease in blood pressure and pulse compared to the control group with a value of p = 0.000 <0.005. This study concludes that Cananga aromatherapy is effective in reducing the anxiety level of patients before tooth extraction in RSGM USU.